2007
DOI: 10.2495/ehr070251
|View full text |Cite
|
Sign up to set email alerts
|

Methods for calculating PNECs using species sensitivity distribution (SSD) with various hypothesis on the way to handle ecotoxicity data

Abstract: Species sensitivity distribution (SSD) methodology is currently used to determine the Predicted No Effect Concentration (PNEC) of a substance, considering chronic ecotoxicological tests on three taxonomic groups: algae, invertebrates and vertebrates (aquatic environment). However, SSD methodology raises some practical questions due to the multiple possibilities of handling the available data. In particular the following points are often discussed: (1) how to take into account the intra-species variation; (2) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The SSD method is based on the assumption that the species being tested is representative of all the species in the ecosystem as far as sensitivity is concerned. It has been shown that the SSD method has the advantages of being supported by statistical theory and being able to use a full array of toxicological data [34]. Therefore, the SSD method might be an effective tool to apply to derive the WQC for silver to protect freshwater aquatic organisms in China.…”
Section: Introductionmentioning
confidence: 99%
“…The SSD method is based on the assumption that the species being tested is representative of all the species in the ecosystem as far as sensitivity is concerned. It has been shown that the SSD method has the advantages of being supported by statistical theory and being able to use a full array of toxicological data [34]. Therefore, the SSD method might be an effective tool to apply to derive the WQC for silver to protect freshwater aquatic organisms in China.…”
Section: Introductionmentioning
confidence: 99%